2011
DOI: 10.1002/adma.201100925
|View full text |Cite
|
Sign up to set email alerts
|

Triggered Cell Release from Materials Using Bioadhesive Photocleavable Linkers

Abstract: A light‐controlled method for cell release by means of surface modification with photolabile linkers is presented. This approach is applicable to any material, provided that the linker is properly designed, and provides direct control over the molecular interactions involved in cell adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
95
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 18 publications
0
95
0
Order By: Relevance
“…[14][15][16] Extended UV exposure is not suitable for bioapplications due to severe phototoxic damage to living cells, [ 17 ] whereas short UV exposure has proven successful in irreversible photoswitching approaches. [ 5 ] Here, we demonstrate a versatile approach that overcomes previous limitations and achieves rapid reversible photoswitching of cell adhesion by biofunctionalized azobenzene surfaces. In order to generate a widely applicable surface coating, we have chosen a covalent binding approach based on generating a coupling layer that is further functionalized with click-chemistry.…”
Section: Doi: 101002/adma201504394mentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16] Extended UV exposure is not suitable for bioapplications due to severe phototoxic damage to living cells, [ 17 ] whereas short UV exposure has proven successful in irreversible photoswitching approaches. [ 5 ] Here, we demonstrate a versatile approach that overcomes previous limitations and achieves rapid reversible photoswitching of cell adhesion by biofunctionalized azobenzene surfaces. In order to generate a widely applicable surface coating, we have chosen a covalent binding approach based on generating a coupling layer that is further functionalized with click-chemistry.…”
Section: Doi: 101002/adma201504394mentioning
confidence: 99%
“…In order to create such dynamic adhesion environments, unidirectional, and irreversible switching of integrin-mediated adhesion has been achieved by light-triggered activation of caged molecules and by electrochemical switching. [5][6][7] Studies using this approach revealed that the time point of cell exposure to adhesion ligands and their density signifi cantly infl uences cell differentiation [ 8 ] and guides vascularization in vivo. [ 9 ] This shows that cells keep track of their adhesion history and that dynamic changes in adhesion signals are imperative in controlling cell functions.…”
Section: Doi: 101002/adma201504394mentioning
confidence: 99%
“…RGD peptides have also been used with a photocleavable linker to provide a photo-responsive surface for cell adhesion and release. Wirkner et al 42 used a photolabile 4,5-dialkoxy 1-(2-nitrophenyl)-ethyl group to attach to the free amine groups of a surface. A tetraethyleneglycol (TEG) spacer was included in the structure enabling the photolabile group to also bind to RGD peptides.…”
Section: Photo-responsive Systemsmentioning
confidence: 99%
“…[3] Thus far, the switchable surfaces have been engineered to respond to an electric field, [4] UV/ Vis light, [5] temperature, [6] chemical stimuli, [7] enzymatic activities, [8] and magnetic field. [9] Among these stimuli, light is highly attractive as it allows control over the cells from a distance with relatively high spatial and temporal precision.…”
mentioning
confidence: 99%